1986
DOI: 10.1021/je00045a008
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities of solid 1,10-decanediol and a solid mixture of 1,10-decanediol and benzoic acid in supercritical carbon dioxide

Abstract: Table IV. Comparison of Experimental Solubilities of Ammonium Bromide and Ammonium Iodide in Liquid Ammonia with Literature Values solubility, wt % solute temp, °C lit.0 obsd6 dev, % ammonium bromide 9.2 69.3 (5) 69.29 -0.01 20.0 69.7 (5) 70.22 . +0.74 32.6 70.4 (5) 71.59 +1.70 53.6 71.2 (5) 72.34 +1.60 25 70.4 (3) 70.75 +0.50 ammonium iodide 2.5 77.2 (5) 77.17 -0.04 22.6 78.6 (5) 78.47 -0.17 44.2 80.0 (5) 79.34 -0.83 57.0 80.9 (5) 81.50 +0.74 25 78.7 (4) 78.64 -0.09 0 (5) Kendall's data; (3) and (4) Hunt's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…Note that anthracene and phenanthrene are miscible over the whole composition range. However, the solubility of each solute was observed to be independent of the weight ratios of pure solids physically mixed in their study, similar to those observed for other eutectic systems [23,24]. This independence may be true for simple eutectic solid mixtures according to the phase rule and the solubility is then independent of the bed composition.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Note that anthracene and phenanthrene are miscible over the whole composition range. However, the solubility of each solute was observed to be independent of the weight ratios of pure solids physically mixed in their study, similar to those observed for other eutectic systems [23,24]. This independence may be true for simple eutectic solid mixtures according to the phase rule and the solubility is then independent of the bed composition.…”
Section: Introductionsupporting
confidence: 79%
“…It is also noted that the fluid phase solubilities become dependent on the feed composition of the solute bed if the co-existed solid solutes undergo melting point depression and produce at least a liquid phase [40,41]. However, for most solid mixture systems, the variation of the extraction feed bed composition has made no difference in the ternary solubility of each solute [23,24,19], where the co-existing solutes retain as pure solid phase under high pressure such as simple eutectic systems.…”
Section: Ternary Solubility and Bed Composition Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, change of the bed composition would make no difference in their ternary solute solubility. The observation of the ternary solubility independent of feed composition has been reported in several investigations [6,26,32]. On the other hand, fluid phase solubilities become dependent on the solute composition of the solid phase if the solutes undergo melting point depression and produce at least a liquid phase.…”
Section: Solubility Behaviormentioning
confidence: 78%
“…However, in this section an attempt is made to predict the solubilities of mixed compounds in supercritical carbon dioxide. Experimental ata provided by: Kosal and Holder [32] for mixed an d thracene and phenanthrene, Pennisi and Chimowitz [26] for mixed 1,10-decanediol and benzoic acid, Iwai el al. [33] for mixed 2,6-and 2,7-dimethylnaphtalenes are used.…”
Section: Ternary Systemsmentioning
confidence: 99%